2007
DOI: 10.1192/apt.bp.106.002840
|View full text |Cite
|
Sign up to set email alerts
|

Why, when and how to ask about childhood abuse

Abstract: ) and a member of the Executive Committee of the International Society for the Psychological Treatments of Schizophrenia (http://www.isps.org). Paul Hammersley is programme director for postgraduate studies in family and individual cognitive-behavioural therapy for psychosis at Manchester University, UK. He has written and lectured extensively on the relationship between childhood trauma and psychosis, and is a member of a multidisciplinary team offering training on how to ask about childhood abuse and researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
181
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(189 citation statements)
references
References 58 publications
4
181
0
4
Order By: Relevance
“…Despite guidelines emphasising the need to routinely assess adversity exposure in psychiatric serviceusers (National Health Service Confederation, 2008), research suggests such recommendations are often not implemented (Read et al 2007;Fisher et al 2011;Hepworth & McGowan, 2013).While staff should not pre-suppose a history of maltreatment unless confirmed by the client, the current findings support the contention that clinicians should receive support and training for making routine evaluations for possible experiences of maltreatment. This is particularly important given the significant under-detection of posttraumatic stress in patients diagnosed with psychosis (Salyers et al 2004;Lommen & Restifo, 2009;Mauritz et al 2013), and that such individuals are less likely to receive an appropriate clinical response (e.g., trauma-focused interventions) relative to those with non-psychotic diagnoses (Agar & Read, 2002;Salyers et al 2004;Grubaugh et al 2011) especially in instances where healthcare workers have strong convictions about biogenetic aetiology (Read & Fraser, 1998;Young et al 2001;Agar & Read, 2002).…”
Section: Discussionmentioning
confidence: 68%
“…Despite guidelines emphasising the need to routinely assess adversity exposure in psychiatric serviceusers (National Health Service Confederation, 2008), research suggests such recommendations are often not implemented (Read et al 2007;Fisher et al 2011;Hepworth & McGowan, 2013).While staff should not pre-suppose a history of maltreatment unless confirmed by the client, the current findings support the contention that clinicians should receive support and training for making routine evaluations for possible experiences of maltreatment. This is particularly important given the significant under-detection of posttraumatic stress in patients diagnosed with psychosis (Salyers et al 2004;Lommen & Restifo, 2009;Mauritz et al 2013), and that such individuals are less likely to receive an appropriate clinical response (e.g., trauma-focused interventions) relative to those with non-psychotic diagnoses (Agar & Read, 2002;Salyers et al 2004;Grubaugh et al 2011) especially in instances where healthcare workers have strong convictions about biogenetic aetiology (Read & Fraser, 1998;Young et al 2001;Agar & Read, 2002).…”
Section: Discussionmentioning
confidence: 68%
“…Read et al (2007) found that amongst clinicians there is a reluctance to enquire about trauma due to fears of vicarious re-traumatisation, feelings of incompetence and anxiety regarding upsetting or distressing the client. Training for clinicians on the assessment of trauma and on evidence-based therapeutic interventions could help promote feelings of professional competency amongst clinicians (Read, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…What does seem to be documented by studies regarding topics identified as "sensitive" is that face-to-face, open-ended research interview settings provide a better frame and result in more disclosure and more detailed reports, than do standardized questionnaires. Also, considerably more disclosure occurs in clinical settings when patients are routinely asked to disclose as compared to when they are not asked [32]. Thus, the obstacles to disclosure of lifetime adversity seem to reside less on the side of the patients.…”
Section: Discussionmentioning
confidence: 99%